Asynchronous Encounters: Artistic Practice and Mediated Intimacy in the Space-Time of Lockdown - Goodwin, Emily; Brophy, Sarah (Edinburgh University Press Journals, 2023)
This essay engages with pandemic-era artistic practice, asking how digital technologies are being taken up out of desires and attempts to be intimate with, proximate to, ‘contemporary’ with one another. Drawing on theories of pandemic temporality and on media analysis approaches that highlight the digital’s materiality, affectivity, and self-reflexivity, we think with three first-person, visual-digital works composed, circulated, and archived during the COVID-19 pandemic: Ella Comberg’s research creation photo-essay on Google Street View, titled ‘Eye of the Storm,’ Bo Burnham’s Netflix streaming special Inside, and Richard Fung’s short documentary film ‘[…],’ shot on iPad. We suggest that these visual-digital pieces open onto the promises and limitations of mediated intimacies – with others, with ourselves, and with the space-time of lockdown. Their commitments to texture and tension draw out the ‘impurity’ (Shotwell 2016) of our digital lifeworlds, while also attuning us to possibilities for ‘waiting with’ (Baraitser and Salisbury 2020) one another amidst what Nadine Chan (2020) calls the ‘distal temporalities’ of late capitalism. To deliberately dwell in stuck or looped time and linger over the touch of distant, distal others – or what we call asynchronous encounters – is not to indulge or excuse the ways in which contemporary media platforms capitalise on affective and creative labour or surveil digital lifeworlds. Instead, we posit that the textures, glitches, and flickering bonds of mediated intimacy may offer new, multiple, reflexive and recursive pathways ‘toward inhabited futures that are not so distal’ (Chan 2020: 13.6).
Keywords: digital media; COVID-19 pandemic; visual arts; materiality; temporality; intimacy